Quantum Computing with Silq Programming : Get up and running with quantum computing with the simplicity of this new high-level programming language /: Get up and running with quantum computing with the simplicity of this new high-level programming language. (2021) - Ganguly, Srinjoy; Cambier, Thomas
No abstract available